Generation of runaway electrons and X rays in an inhomogeneous electric field at high gas pressures; Laser and Particle Beams; Vol. 34, iss. 4 - Tarasenko V. F. Victor Fedotovich; Baksht E. Kh. Evgeny Khaimovich; Beloplotov D. V. Dmitry Viktorovich; Burachenko A. G. Aleksandr Gennadjevich; Lomaev M. I. Mikhail Ivanovich; Sorokin D. A. Dmitry Aleksandrovich (2016, 2016)
Title screen